2022
DOI: 10.1101/2022.04.12.488068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An updatedC. elegansnuclear body muscle transcriptome for studies in muscle formation and function

Abstract: The body muscle is an important tissue used in organisms for proper viability and locomotion. The contractile unit of the muscle is the sarcomere, which is ultimately responsible for the contraction reaction leading to movement. Although this tissue is generally well studied and characterized, and many pathways have been elucidated throughout the years, we still lack a comprehensive understanding of its transcriptome, and how it controls muscle development and function. Here, we have updated a nuclear FACS sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 58 publications
(109 reference statements)
2
6
0
Order By: Relevance
“…Our results overlap with three previous miR-NAomic studies of worm tissues with more miRNAs identified (Supplementary Fig. 1, Supplementary Data 2) [25][26][27] . Of the miRNAs reported in miRbase, 113 are considered highly confident 28 , and we detected 83 of them.…”
Section: Ageing Changes Mirnaomes In C Elegans Tissuessupporting
confidence: 87%
See 3 more Smart Citations
“…Our results overlap with three previous miR-NAomic studies of worm tissues with more miRNAs identified (Supplementary Fig. 1, Supplementary Data 2) [25][26][27] . Of the miRNAs reported in miRbase, 113 are considered highly confident 28 , and we detected 83 of them.…”
Section: Ageing Changes Mirnaomes In C Elegans Tissuessupporting
confidence: 87%
“…One is to immunoprecipitate Argonaute (AGO) protein expressed tissuespecifically and profile the associated miRNAs 26 . The last one is through FACS of the nucleus which are labelled using tissue-specific fluorescent proteins 27 . None of the methods directly profile miRNAs in the worm cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the years, our lab has refined the 3'UTR collection in C. elegans in the whole animal and in several somatic tissues in various stages of development 10,13,14,24,26,27 (Main Figure 1B).…”
Section: Introductionmentioning
confidence: 99%